Evaluation of persistent-mode operation in a superconducting MgB2 coil in solid nitrogen. (22nd February 2016) - Patel, Dipak; Al Hossain, Md Shahriar; See, Khay Wai; Qiu, Wenbin; Kobayashi, Hiroki; Ma, Zongqing; Kim, Seong Jun; Hong, Jonggi; Park, Jin Yong; Choi, Seyong; Maeda, Minoru; Shahabuddin, Mohammed; et al.
Abstract: We report the fabrication of a magnesium diboride (MgB2 ) coil and evaluate its persistent-mode operation in a system cooled by a cryocooler with solid nitrogen (SN2 ) as a cooling medium. The main purpose of SN2 was to increase enthalpy of the cold mass. For this work, an in situ processed carbon-doped MgB2 wire was used. The coil was wound on a stainless steel former in a single layer (22 turns), with an inner diameter of 109 mm and height of 20 mm without any insulation. The two ends of the coil were then joined to make a persistent-current switch to obtain the persistent-current mode. After a heat treatment, the whole coil was installed in the SN2 chamber. During operation, the resultant total circuit resistance was estimated to be <7.4 × 10 −14 Ω at 19.5 K ± 1.5 K, which meets the technical requirement for magnetic resonance imaging application.